Non-antibiotic prevention and treatment against Acinetobacter baumannii infection: Are vaccines and adjuvants effective strategies? - Hu, Yue; Zhang, Xianqin; Deng, Shanshan; Yue, Changwu; Jia, Xu; Lyu, Yuhong (Frontiers in Microbiology, 2023)
Acinetobacter baumannii (A. baumannii) is a Gram-negative opportunistic pathogen widely attached to the surface of medical instruments, making it one of the most common pathogens of nosocomial infection, and often leading to cross-infection and co-infection. Due to the extensive antibiotic and pan-resistance, A. baumannii infection is facing fewer treatment options in the clinic. Therefore, the prevention and treatment of A. baumannii infection have become a tricky global problem. The requirement for research and development of the new strategy is urgent. Now, non-antibiotic treatment strategies are urgently needed. This review describes the research on A. baumannii vaccines and antibacterial adjuvants, discusses the advantages and disadvantages of different candidate vaccines tested in vitro and in vivo, especially subunit protein vaccines, and shows the antibacterial efficacy of adjuvant drugs in monotherapy.